The second coefficient of the Alexander polynomial as a satellite obstruction - Lewark, Lukas (Comptes Rendus. Mathématique)
A set $\mathcal{P}$ of links is introduced, containing positive braid links as well as arborescent positive Hopf plumbings. It is shown that for links in $\mathcal{P}$, the leading and the second coefficient of the Alexander polynomial have opposite sign. It follows that certain satellite links, such as $(n,1)$-cables, are not in $\mathcal{P}$.